Two new species and a new record of Hypoxylaceae (Xylariales, Ascomycota) from Mexico - Pamela E. Reyes; Juan Pablo Pinzón; Ricardo Valenzuela; Tania Raymundo; Juan Tun-Garrido; Ricardo García-Sandoval (MycoKeys)
The family Hypoxylaceae has a cosmopolitan distribution with greater diversity in tropical regions, its growth habit is saprotrophic, endophytic and potentially phytopathogenic. From the revision of herbarium specimens and field collections from the Yucatan Peninsula, two new species were described: Annulohypoxylon fusisporum, characterized by having fusiform spores and Hypoxylon xmatkuilense which is distinguished by having stromata vinaceous and dark brown KOH-extractable pigments. The species are described based on morphological characters and Bayesian Inference analyses of four molecular markers (ITS, LSU, RPB2 and TUB2). In addition, one new record from Mexico is presented: Hypoxylon bellicolor. The presence of Daldinia eschscholtzii, H. lenormandii, H. lividipigmentum and Entonaema liquescens is confirmed with molecular data.